2001
DOI: 10.1161/01.hyp.37.3.911
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Spontaneous Baroreflex Sensitivity in a Healthy Working Population

Abstract: Abstract-Baroreflex sensitivity (BRS) by the spontaneous sequence technique has been widely used as a cardiac autonomic index for a variety of pathological conditions. However, little information is available on determinants of the variability of spontaneous BRS and on age-related reference values of this measurement in a healthy population. We evaluated BRS as the slope of spontaneous changes in systolic blood pressure (BP) and pulse interval from 10 minutes BP (Finapres) and ECG recordings in 1134 healthy vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
89
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 29 publications
17
89
3
8
Order By: Relevance
“…Kardos et al [21] found that age, heart rate, systolic and diastolic blood pressure, gender, body mass index and smoking were independent ‘physiological’ predictors of BRS in a large population of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Kardos et al [21] found that age, heart rate, systolic and diastolic blood pressure, gender, body mass index and smoking were independent ‘physiological’ predictors of BRS in a large population of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The R-R intervals obtained from the raw ECG and the SBP signals were subjected to BRS analysis using the Sequence Method. 21 Simultaneous unidirectional increase/decrease of R-R intervals and systolic blood pressure (SBP) values in a sequence were identified for a minimum of three consecutive beats. The BRS was computed as the ratio DR-R/DBP (ms mmHg )1 ) during baseline, tonic and recovery periods using three or more increasing sequences within the continuous heart rate (HR) and SBP time series.…”
Section: Analysis Techniquesmentioning
confidence: 99%
“…≥4 years caregiving, N=40), with non-caregivers (N = 50) serving as the reference group with whom the other groups were contrasted. Because older age [28], female gender [28, 29], higher body mass index (BMI) [30, 31], infrequent exercise [32], smoking history [33, 34], use of anti-hypertensive medications [35, 36], history of cardiovascular disease [3740], and resting heart rate [41] have been associated with worsened cBRS, we included all of these variables as covariates in our regression model. To ensure multivariate normality, unstandardized residuals from the multivariate linear regression were tested via the Kolmogorov-Smirnov test.…”
Section: Methodsmentioning
confidence: 99%